2008
DOI: 10.1149/1.2982898
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization and Micro Structure Diagnostics of Glass Frit Bonded Interfaces

Abstract: In this paper, results of mechanical strength investigations for glass frit bonded components using tensile and micro chevron testing are presented. Specific attention is given to the formation of lead precipitates close to the glass-silicon interface which affects the strength properties and form reliability risks. Results of the accompanying SEM and TEM investigations suggest that the lead precipitation can be understood in terms of a redox reaction involving the oxidation of the Si wafer and can be reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In the absence of the knowledge about the effective bonding geometry (i.e., as obtained from process), wrong conclusions would be inferred from the tests. For [ 17 ], lead precipitates in the gf layer can reduce the strength at the gf-Si interconnection during tensile tests, while their influence appeared lower in micro-chevron tests. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of the knowledge about the effective bonding geometry (i.e., as obtained from process), wrong conclusions would be inferred from the tests. For [ 17 ], lead precipitates in the gf layer can reduce the strength at the gf-Si interconnection during tensile tests, while their influence appeared lower in micro-chevron tests. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, glass frit bonds also had shortcomings in terms of the wide bonding rim (>200 µm) and the possible introduction of contaminations (Pb, Bi, etc.) to the components [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient bonding pressure also causes the occurrence of voids at the uneven bonding interface [11]. For the native silicon substrate and a cap wafer without an intermediate layer such as oxide and nitride, the formation of small spherical lead precipitations in the fracture plane results in a large number of voids [12,13]. Ser Choong Chong et al [14] found that after annealing the oxide layer on the cap layer before bonding, there were almost no holes in the interface between the glass paste ring and the cap layer.…”
Section: Introductionmentioning
confidence: 99%